Speech Perception and Audiometry Thresholds in Nucleus Cochlear 22 and Nucleus 24 Implant Users - Samuel, Paola Angelica; Gomez, Maria Valéria Schmidt Goffi; Lopes, Débora Maria Befi; Matas, Carla Gentile; Tsuji, Robinson Koji; Neto, Rubens Vuono de Brito; Bento, Ricardo Ferreira (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: Clinically it was observed the contribution of the Nucleus 24 (N24) cochlear implant (CI) technology. The confirmation of this evidence would be important because it affects directly the indication criteria of the cochlear implant.Objective: To verify the contribution of the technology's updating of the CI about the auditory thresholds and the performance in the perception of sentences after 12 mouths of implant use.Method: A retrospective, cross-sectional study with database collection. Selection criteria: age equal or higher than 18 years old, CI N22 or N24 device use, auditory privation time until 20 years, which deafness etiology does not be meningitis. The sample was divided into G22 (N22 users), and G24 (N24 users). The groups were compared concerning the result in the sentences perception test in the silence and audiometric thresholds after 12 mouths of use.Results: From 84 adults patients selected, 54 filled the selection criteria, being 13 users of N22 and 41 users of N24. There was no difference statistically significant between preoperative auditory residues and time of auditory privation of the N22 and N24 users. The N24 users presented best averages in the audiometric thresholds, but the sentences perception tests in the silence do not indicated difference between models.Conclusion: The contribution of the technology was evidenced only in the auditory thresholds. News studies are being performed in order to evaluate the technology contribution in the speech perception in auditory situations more difficult.
Keywords: cochlear implant; hearing; hearing loss; auditory tests; speech perception